Ottoman transcultural memories: Introduction. (October 2019) - Koureas, Gabriel; Prosser, Jay; Wilson, Colette; Hakim-Dowek, Leslie
This introduction lays out the context and aims for the special issue's focus on Ottoman transcultural memories. We explain the pertinence of transcultural memories for the Ottoman Empire, and we discuss contemporary politicizations of Ottoman nostalgia, or neo-Ottomanism. We define the key terms in our analyses, rooting our approach in memory studies, and distinguishing a transcultural approach to memory from comparable approaches in postcolonial studies. The introduction further sets out how the special issue refigures memory studies, transcultural and Ottoman studies. The issue's contents are outlined, with the interdisciplinary and transmedial contributions necessarily driven by the diverse archives of Ottoman transcultural memories. Creative selections are informed by the affective resonance of Ottoman transcultural memories, in turn refiguring postmemory.